2011
DOI: 10.1007/s11852-011-0149-0
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of alien plant species along the Romanian Black Sea coastal area. The role of harbours

Abstract: Previous studies have found a higher proportion of alien plant species along the coastal area of the Black Sea. The goals of the present study were to assess the role of two harbours as gateways and reservoirs for alien plant species, to compare the structure and invasion pattern of the alien plants recorded there, and test methods useful for effective monitoring programs. We inventoried 12 sites along the western Black Sea coast from the harbour of Sulina in the north to Cape Kaliakra in the south. Each site … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 15 publications
0
8
0
1
Order By: Relevance
“…Anastasiu et al [29] assessed the role of the harbours as gateways and reservoirs for alien plant species, the structure and invasion pattern of the alien plants, and test methods useful for effective monitoring programs; on the other hand Sava et al [30] showed the influence of the nutrients on the macrophytic red algae of the Romanian Black Sea coast.…”
Section: The Expected Impact Of the Wave Dragon Farm On The Marinementioning
confidence: 99%
“…Anastasiu et al [29] assessed the role of the harbours as gateways and reservoirs for alien plant species, the structure and invasion pattern of the alien plants, and test methods useful for effective monitoring programs; on the other hand Sava et al [30] showed the influence of the nutrients on the macrophytic red algae of the Romanian Black Sea coast.…”
Section: The Expected Impact Of the Wave Dragon Farm On The Marinementioning
confidence: 99%
“…Port areas have been extensively explored with respect to marine invasive species (Molnar et al 2008). Attention has also been paid to terrestrial plant species, which can also benefit from marine/ freshwater transportation routes (Anastasiu et al 2011;Jehlík 2013). The presence of alien plants among the flora of seaports in the north of Europe has been reported for Poland (Ćwikliński 1970;Misiewicz 1985), Norway (Ouren 1978(Ouren , 1980(Ouren , 1983(Ouren , 1987, Germany (Jehlík 1981(Jehlík , 1989(Jehlík , 1994a, the Netherlands (Jehlík and Dostálek 2015), and Ireland (Reynolds 1990).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of alien plants among the flora of seaports in the north of Europe has been reported for Poland (Ćwikliński 1970;Misiewicz 1985), Norway (Ouren 1978(Ouren , 1980(Ouren , 1983(Ouren , 1987, Germany (Jehlík 1981(Jehlík , 1989(Jehlík , 1994a, the Netherlands (Jehlík and Dostálek 2015), and Ireland (Reynolds 1990). Information on the occurrence of alien plants in the Black Sea ports in the territory of Ukraine is reported by Petryk (1993), and the role of ports in the spread of alien plants along the Romanian Black Sea was analysed by Anastasiu et al (2011). In addition, the relationship between the occurrence of alien plants and urban habitat type in the port of Trieste on the Adriatic coast was explored in detail by Tordoni et al (2017).…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, escaped populations of D. innoxia have mostly been found at roadsides and different types of ruderal habitats. It has been recorded in most countries of Southern and Central Europe as well as in some countries of Northern Europe: Austria (Essl & Rabitsch 2002), Belgium (Verloove 2006), Bulgaria (Greuter & Raus 2005), Croatia (Franjić 1993;Pandža & Stančić 1999;Pandža et al 2001), Czech Republic (Danihelka et al 2012), European Turkey (Vladimirov et al 2013), France (Kerguélen 1999), Great Britain (Sell & Murrell 2009), Greece (Arianoutsou et al 2010), Italy (Pignatti 1982), Lithuania (Gudžinskas 2017), Montenegro (Caković et al 2014), Norway (Gederaas et al 2012), Portugal (Almeida & Freitas 2001), Romania (Anastasiu et al 2011), Russia (Seregin 2014), Spain (Castroviejo et al 2012, Serbia (Lakušić et al 2017), Slovakia (Medvecká et al 2012), Slovenia (Martinčič et al 1999), Sweden (Karlsson 1997) and Ukraine (Mosyakin & Fedoronchuk 1999). In the Mediterranean region D. innoxia has established, whereas in other regions it is ascribed to the group of casual species.…”
Section: Recent Chorological Data On Cultivation and Garden Escapingmentioning
confidence: 99%